Ukhuwah Islamiyah as an Islamic Organizational Value: Synthesizing Evidence from Islamic Boarding School Contexts Using PICOS - Aziz, Akbar Nur; M. Suud, Fitriah; Purnomo, Halim; Nashori, Fuad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This research aims to reconstruct the value of Ukhuwah Islamiyah as a cultural system in Islamic organizations, grounded in the local values of Islamic boarding schools through the Panca Jiwa Pondok framework. Islamic organizations, especially pesantren, face challenges in aligning traditional values with contemporary organizational practices. A systematic review using the PICOS approach was conducted, analyzing 23 quantitative studies retrieved from Scopus and Google Scholar. The findings reveal four key dimensions of Ukhuwah Islamiyah in organizational settings: spiritual bonding, collective empathy, relational leadership, and deliberation. These dimensions significantly enhance organizational commitment, job satisfaction, loyalty, and Islamic performance across pesantren, madrasah, and Islamic higher education institutions. The study contributes by offering a novel conceptual model of Organizational Ukhuwah that integrates Panca Jiwa Pondok’s traditional values with contemporary organizational psychology. This model provides practical guidance for pesantren leaders and policymakers to foster inclusive decision-making, strengthen leadership training, and build a supportive climate based on spiritual and collective values. The research suggests further exploration of the practical implementation of this model in diverse Islamic institutions.